The Legal Position of Investigators under Law Number 20 of 2025 on the Indonesian Criminal Procedure Code - Isdar (Punggawa Legacy Center, 2026)
This article examines the legal position of investigators under Law Number 20 of 2025 on the Indonesian Criminal Procedure Code. The statute redefines investigation as a structured evidentiary process and places investigators as key actors who determine whether a reported event may proceed to prosecution. Using normative legal research, this study analyzes provisions on investigator classification, evidentiary authority, suspect determination, coercive measures, restorative justice, digital evidence, legal assistance, and pretrial review. The analysis shows that Articles 1, 6, 7, 89, 90, 142, 158, and 163 construct investigators as authoritative but reviewable procedural actors. Their authority covers evidence collection, rights affecting measures, settlement facilitation, and coordination with prosecutors. However, such authority is limited by due process, proportionality, documentation, judicial control, victim protection, and suspect rights. The new KUHAP therefore positions investigators as legal gatekeepers of legality, fairness, and accountability within Indonesian criminal justice.